Influencia de los youtubers extranjeros en el lenguaje social de los estudiantes de nivelación (CANU) de la UTB 2019) - Salvatierra Almeida, Yuli Elizabeth (2019)
Nowadays, easy access to the internet, computers and similar devices created thanks to technological innovations has produced a cybernetic revolution. The “YouTube” platform created a universe for people, it was the first web portal to search for videos and creativity originated the birth of the Youtubers. At the moment, similar research has been carried out according to (Freire, 2018) “YouTubers can generate some influence on their subscribers” with this case study we will be able to measure the influence of YouTubers on the social language of the students of leveling (CANU) of the UTB 2019) what will allow us to take or recommend measures to reduce the use of inappropriate, offensive or discriminatory language. At the conclusion of this work we have determined that youtuber influence the social language of students, since that 52.4% of the students of leveling (CANU) of the UTB 2019 accept that they are influenced in their way of speaking either with phrases or with gestures. When being influenced by YouTubers, it is advisable to raise awareness of the ambiguities of the language, to soon make an online campaign where the use of words is respected and that this is also virtualized by social networks so that it has greater reach